Complications following endoscopic retrograde cholangiopancreatography: minimal invasive surgical recommendations. - Bora Koc; Huseyin Yuce Bircan; Gokhan Adas; Ozgur Kemik; Adem Akcakaya; Alpaslan Yavuz; Servet Karahan (PLoS ONE)
Background ERCP has a complication rate ranging between 4% and 16% such as post-ERCP pancreatitis, hemorrhage, cholangitis and perforation. Perforation rate was reported as 0.08% to 1% and mortality rate up to 1.5%. Besides, injury related death rate is 16% to 18%. In this study we aimed to present a retrospective review of our experience with post ERCP-related perforations, reveal the type of injuries and management recommendations with the minimally invasive approaches. Methods Medical records of 28 patients treated for ERCP-related perforations in Okmeydani Training and Research Hospital between March 2007 and March 2013 were reviewed retrospectively. Patient age, gender, comorbidities, ERCP indication, ERCP findings and details were analyzed. All previous and current clinical history, laboratory and radiological findings were used to assess the evaluation of perforations. Results Between March 2007 and March 2013, 2972 ERCPs were performed, 28 (0.94%) of which resulted in ERCP-related perforations. 10 of them were men (35.8%) and 18 women (64.2%). Mean age was 53.36 ± 14.12 years with a range of 28 to 78 years. 14 (50%) patients were managed conservatively, while 14 (50%) were managed surgically. In 6 patients, laparoscopic exploration was performed due to the failure of non-surgical management. In 6 of the patients that ERCP-related perforation was suspected during or within 2 hours after ERCP, underwent to surgery primarily. There were two mortalities. The mean length of hospitalization stay was 10.46 ± 2.83 days. The overall mortality rate was 7.1%. Conclusion Successful management of ERCP-related perforation requires immediate diagnosis and early decision to decide whether to manage conservatively or surgically. Although traditionally conventional surgical approaches have been suggested for the treatment of perforations, laparoscopic techniques may be used in well-chosen cases especially in type II, III and IV perforations.